Spatiotemporal Signal Processing in Automobile Radar Subject to Active Interference - Ermolaev, V. T.; Semenov, V. Yu; Flaksman, A. G. (Radiophysics and quantum electronics, 2024)
We consider an automobile radar of millimeter wave lengths with phase-shift keyed (PSK) probing signals operating under the influence of active interference whose sources are radars of other vehicles. We propose a method of spatiotemporal processing which allows one to detect and estimate the parameters (range, velocity, and bearing) of the surrounding vehicles, which can simultaneously be both interference-free targets (own radar is turned off) and interference targets (own radar is turned on). We study the case where both linear frequency-modulated (LFM) and phasemodulated (PM) signals can be interference. The numerical-simulation results are presented, showing the high efficiency of the proposed method in terms of the probability of simultaneous detection of near and far interference and interference-free targets.